2015
DOI: 10.1111/ffe.12337
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue limit of induction hardened railway axles

Abstract: A B S T R A C T A new surface induction hardening technology was designed for the purpose of increasing the resistance of railway wheelsets to fatigue damage. This paper gives a detailed presentation of the technological aspects of induction hardening of axles. The increased fatigue resistance in hardened surfaces compared with standard heat treatment of EA4T steel was verified using tensile test specimens, press-fitted wheel seat/axle joints at 1:3 scale and press-fitted wheel/axle joints at actual size. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Generally the maximum in-service stress amplitude is less pronounced than 200 MPa, which is far lower than allowable stress of full-scale axle used 34CrNiMo6 [17,22]. Such nature actually suggests that the axle is subjected to typical elastic deformation according to nominal stress approach.…”
Section: Crack Growth Modelmentioning
confidence: 98%
See 2 more Smart Citations
“…Generally the maximum in-service stress amplitude is less pronounced than 200 MPa, which is far lower than allowable stress of full-scale axle used 34CrNiMo6 [17,22]. Such nature actually suggests that the axle is subjected to typical elastic deformation according to nominal stress approach.…”
Section: Crack Growth Modelmentioning
confidence: 98%
“…In addition, the induction hardening can achieve a relatively small stress gradient and uniform hardness distribution, which can effectively prevent the nearsurface material from debonding. Such technological advantage throw more prospective action against fatigue crack initiation and casual propagation of full-scale axles [14,15,22].…”
Section: Axle Surface Hardeningmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies suggested that the fatigue strength of a material is proportional to its tensile strength and the fatigue crack that results in final failure usually initiates at the surface of the material [1][2][3]. In order to upgrade the fatigue strength of engineering materials/components, investigators have used surface strengthening techniques in the applications of aviation, automobile and high-speed railway [4][5][6][7][8][9]. The methods of surface treatment, such as shot peening, nitriding and surface induction, produce a strengthened surface layer which always possesses a gradient feature of microstructure and mechanical behavior including residual stress from the surface to the interior of treated specimens or components.…”
Section: Introductionmentioning
confidence: 99%
“…Fajkoš et al [5] reported that the fatigue strength of an EA4T steel (25CrMo4) with surface induction treatment had an increase of 70% compared to that with standard heat treatment. Roland et al [7] and Yang et al [8] showed that a stainless steel with surface mechanical attrition treatment and a pure Cu with surface mechanical grinding treatment had higher fatigue strength than the original materials, especially in high cycle fatigue regime.…”
Section: Introductionmentioning
confidence: 99%